Answer:
y = -2x + 6
Step-by-step explanation:
Using
y - y_1 = m(x - x_1)
First, find the slope
2y - x = 1
Following this eqn
y = mx + C
2y = 1 + x
To get y, divide through by 2
2y/ 2 = (1 +x) / 2
y = 1+x/2
y = 1/2 + x /2
y = 1/2x + 1/2
Note, if two lines are perpendicular, their slope will be negative reciprocal
Slope = m = -2/1
Using this y - y_1 = m(x - x_1)
With point( 4 , -2)
x_1 = 4
y_1 = -2
y - (-2) = -2/1( x - 4)
y + 2 = -2/1(x - 4)
y + 2 = -2x + 8
y = -2x + 8 - 2
y = -2x + 6
The eqn of the line is
y = -2x + 6